NEW USM INNOVATION: HEAD-BUN SAVES PROCEDURAL COST OF ENDOTRACHEAL INTUBATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUBANG KERIAN, 25 May 2015 – Universiti Sains Malaysia (USM) has successfully introduced an apparatus which could reduce the cost in administering the procedure of Endotracheal Intubation, which is the insertion of a tube into a patient’s breathing cavity to assist in breathing, as the patient could no longer breathe on his or her own during the anaesthesization process in the Operations Theatre.